Biblical Basis and Historical Antecedence of Tithing in the Christian Church - Blasius Abin; Aristas S. Pasuhuk (Jurnal Ilmiah Wahana Pendidikan, 2023)
The issue of tithing in the Christian church has become an object of debate at the pragmatic and academic levels. Due to the rejection of this Biblical practice, the ultimate purpose of this article is to investigate Bible references as well as the historical basis of the practice of tithing in the Christian church. The chronology of the discussion is as follows: The first section is to investigate Old Testament texts as theological references and praxis of the tithing. The second section focuses on the discussion of the discontinuity element of the practice in the Christian church. The third section is the conclusion and synthesis. The following is the synthesis and conclusion of the research. First, tithing does not only apply to a certain historical period or is practiced by certain ethnic groups. On the contrary, those who believe in God as a Creator and Saviour inherently recognize that tithing is simply about a relationship with God. Second, tithing is closely related to the worship of God as well as faith in God as the Creator and Redeemer. Hence, the theology of tithe is a product of one's faith and relationship with God. Third, there are differences in the praxis levels of Old Testament and New Testament tithing but do not reduce the basic theological principles of tithing, namely it belongs to God. Thus, there is no reference in the New Testament literature that strengthens the argument on which the tithe has been eradicated in the Christian Church. On the contrary, Jesus ratified the practice of tithing. This was confirmed by the practice of believers in the period of the post-apostolic church.